Buffalo nasal odorant-binding protein (bunOBP) and its structural evaluation with putative pheromones - Muthukumar, Subramanian (2018)
Pheromones are odoriferous volatile chemical cues produced by animals for communication among conspecifics so as to regulate their social behaviors. In general, the odor compounds are recognized by receptors in the nasal cavity. Odorant-binding protein (OBP), a lipocalin family protein, mediates the air-borne odor cues to nasal receptors through nasal mucus. The presence of OBP in several mammalian species is well documented but to-date there is no report of a nasal OBP in buffalo. Hence, the present study was undertaken to investigate if OBP is present in buffalo nasal mucus. Uni- and two-dimensional gel electrophoresis of the nasal mucus suggested the presence of OBP, which was confirmed using mass spectrometry. In silico homology model of the OBP was generated and its structural similarity with other mammalian OBPs was assessed. Finally, molecular-docking and -dynamics simulations analysis revealed the efficiency of buffalo nasal OBP (bunOBP) to bind with buffalo pheromones as well as other reported chemical cues. Taken together, the occurrence of nasal OBP in buffalo and its putative role in odor binding are reported for the first time. The potential association of this protein with estrus-specific volatiles could be taken to advantage for non-invasive detection of estrus in buffaloes.